Deciphering the Underlying Mechanisms of Formula Le-Cao-Shi Against Liver Injuries by Integrating Network Pharmacology, Metabonomics, and Experimental Validation - Zhao, Qing; Ren, Xia; Song, Shu-Yue; Yu, Ri-Lei; Li, Xin; Zhang, Peng; Shao, Chang-Lun; Wang, Chang-Yun (Frontiers in Pharmacology, 2022)
Le-Cao-Shi (LCS) has long been used as a folk traditional Chinese medicine formula against liver injures, whereas its pharmacological mechanisms remain elusive. Our study aims to investigate the underlying mechanism of LCS in treating liver injures via integrated network pharmacology, metabonomics and experimental validation. By network pharmacology, 57 compounds were screened as candidate compounds based on ADME parameters from LCS compound bank (213 compounds collected from the literature of three single herbs). According to online compound-target databases, the above candidate compounds were predicted to target 87 potential targets related with liver injuries. More than 15 pathways connected with these potential targets were considered as vital pathways in collectively modulating liver injuries, which were found to be relevant with cancer, xenobiotics metabolism by cytochrome P450 enzymes, bile secretion, inflammation and anti-oxidation. Metabonomics analysis by using the supernatant of rat liver homogenate with UPLC-Q-TOF/MS demonstrated that 18 potential biomarkers could be regulated by LCS which were closely related to linoleic acid metabolism, glutathione metabolism, cysteine and methionine metabolism, and glycerophospholipid metabolism pathways. Linoleic acid metabolism and glutathione metabolism pathways were two key common pathways in both network pharmacology and metabonomics analysis. In the ELISA experiments with CCl4 induced rat liver injury model, LCS was found to significantly reduce the levels of inflammatory parameters, decrease liver malondialdehyde (MDA) level, and enhance the activities of hepatic antioxidant enzymes, which validated that LCS could inhibit liver injuries through anti-inflammatory, suppressing lipid peroxidation, and improving antioxidant defense system. Our work could provide new insights in the underlying pharmacological mechanisms of LCS against liver injuries, which is beneficial for its further investigations and modernization.